(untitled) (International Congress on Economics, Management and Business Studies, 2026)
Atrial fibrillation (AF) is one of the most common arrhythmias among cardiovascular diseases and significantly increases the risk of thromboembolic complications, particularly stroke. Anticoagulant therapy is the main method of reducing thromboembolic risk in AF patients. Rivaroxaban, a direct factor Xa inhibitor, is an effective and convenient drug. Assessing its efficacy and safety is highly relevant.